Hubungan antara Tingkat Pendidikan dengan Kecemasan pada Wanita Menopause - Puspitasari, Ayu Wening Tyas; Indrayanto, Yoseph .; Dharmawan, Ruben . (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background:Menopausal syndrome is experienced by many women around the world. Most women who experience menopause will feel the menopause as a problem or disorder. Nevertheless, menopause is a normal transition period, but if it is not properly handled will cause psychological, physical, and social disorders which can affect the quality of life for women. One of the general psychological disorder is anxiety. Many factors affect the anxiety of menopausal women, one of them is knowledge. The higher education level of the person will be more receptive to information so that the more knowledge. Therefore, the anxiety experienced will be lighter. This study aims to determine the relationship between the anxiety and educationlevel ofmenopausal women. Methods: This researchwas analytic observational with cross sectional approach. The population was all menopausal women in Posyandu Dahlia RW 19Nusukan, Posyandu RW 14 Nusukan, and PosyanduDahlia RW 13 Pucangsawit. The sample selection used purposive random sampling technique. The sample number was 30 women. The research instrumentswere questionnairesLie-Multyphasic Minnesota Personality Inventory (L-MMPI) and Tailor Manifest Anxiety Scale (TMAS). The data were Â analyzed using theSpearman correlation test. Results: Correlation between the level of education and anxiety was-0.431 (p = 0.017). Conclusions: The conclusion from this research is the majority of the subject experience moderate level of anxiety. There is negative correlation between the level of education and anxiety.The higher of the education level of the subjects, the lower of the level of anxiety, and the lower of education level of the subjects, the higher of the level of anxiety. Keywords: Menopause, anxiety level, education level, correlationÂ